2018
DOI: 10.1016/j.clinthera.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody Biosimilars in Oncology: Critical Appraisal of Available Data on Switching

Abstract: From the scarce data available, the consequences of switching between reference product mAbs and their biosimilar(s) in the oncology setting are as yet unknown. Additional clinical evidence from well-designed switching studies is needed to guide switching decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…This systematic literature review aims to synthesize the currently available data on switching and to assess the safety, immunogenicity, and efficacy of switching between RPs and their respective biosimilar version(s). This review broadens the scope of previous studies 14,17 by reviewing switch data for biologicals of every therapeutic class for which a European market authorization has been granted, more specifically: (i) recombinant human growth hormones (rhGHs), (ii) erythropoietins, (iii) granulocyte colony stimulating agents, (iv) insulins, (v) tumor necrosis factor alpha inhibitors (anti-TNFs), (vi) gonadotropins, (vii) low-molecular-weight heparins, and (viii) mAbs used in oncology. Further, we aim to provide a critical insight on the current state-of-the-art related to switching.…”
Section: Key Concepts and Terminologymentioning
confidence: 76%
See 1 more Smart Citation
“…This systematic literature review aims to synthesize the currently available data on switching and to assess the safety, immunogenicity, and efficacy of switching between RPs and their respective biosimilar version(s). This review broadens the scope of previous studies 14,17 by reviewing switch data for biologicals of every therapeutic class for which a European market authorization has been granted, more specifically: (i) recombinant human growth hormones (rhGHs), (ii) erythropoietins, (iii) granulocyte colony stimulating agents, (iv) insulins, (v) tumor necrosis factor alpha inhibitors (anti-TNFs), (vi) gonadotropins, (vii) low-molecular-weight heparins, and (viii) mAbs used in oncology. Further, we aim to provide a critical insight on the current state-of-the-art related to switching.…”
Section: Key Concepts and Terminologymentioning
confidence: 76%
“…2 Further, other reviews have been conducted but these mostly focussed on one specific product class or therapeutic area. 17,70,71 Two other systematic literature reviews (McKinnon and Cohen 72,73 ) have been published that included switch studies derived from multiple product classes and disease areas. Switch studies were included until June of 2017 in these reviews.…”
Section: Current Switch Evidence -Learnings and Considerationsmentioning
confidence: 99%
“…Generics and biosimilars can help to improve the cost‐effectiveness of cancer drugs and make them accessible to more patients . Table summarizes the differences between generics and biosimilars.…”
Section: Approaches To Decreasing Cancer Medicine Costsmentioning
confidence: 99%
“…Assessing the effects of switching in a "real-world" setting can be challenging, as patients may be switched back and forth among different products in clinical practice [23]. Observational studies of the use of epoetins and granulocyte colony-stimulating factors in patients with chronic kidney disease or cancer in Italy have demonstrated that there is frequent switching between different biological products belonging to the same class in routine clinical care [24,25].…”
Section: Current Evidence On the Effects Of Switchingmentioning
confidence: 99%